Hop Waste Seed Coating (Pilling) as Circular Bioeconomic Alternative to Improve Seed Germination and Trichoderma Development - Sara Mayo-Prieto; Alejandra J. Porteous-Álvarez; Guzmán Carro-Huerga; Laura Zanfaño; Daniela Ramírez-Lozano; Álvaro Rodríguez-González; Alicia Lorenzana de la Varga; Pedro A. Casquero (Agriculture)
This study investigates the use of hop cone residues as a sustainable alternative to peat in seed coating formulations for the delivery of biocontrol agents such as Trichoderma. Some native isolates, T. velutinum T029 and T. harzianum T019 and T059, were tested for their development on peat and hop residues using qPCR. The results showed significantly higher fungal growth in hop cones, indicating their value as a carbon-rich substrate. Seed germination tests on various species showed that hop-based coatings did not inhibit germination and in some cases improved it. Field trials confirmed that bean seeds coated with hops 24 h before sowing outperformed those coated with peat, particularly in integrated production systems, in terms of germination. The results of this study suggest a new area of research: using hop residues in sustainable seed treatments could promote the valorization of agricultural residues, while improving crop establishment and reducing the dependence on synthetic inputs.